Effects of acute caffeine intake on sex hormones response and repetitions to failure in resistance-trained females during early follicular phase - AbuMoh`d, M. (Journal of Human Sport & Exercise, 2023)
This study investigated the acute effects of caffeine intake on sex hormones (follicle-stimulating hormone, luteinizing hormone, prolactin, oestradiol, and progesterone) following resistance exercise performance during the early follicular phase. In addition, the total number of failed repetitions was determined. Ten resistance-trained females performed two consecutive trials (48 h apart). Participants were randomly assigned to receive either caffeine (4 mg/kg) 1 h before exercise or a placebo, using a double-blind crossover design. Each trial included the following resistance exercises: chest press, lat pulldown, triceps pushdown, and rowing torso. Each exercise was performed in three sets of 10 repetitions at 60% of 1-RM, with a 90 s recovery interval, followed by repetitions to failure at the same intensity during the fourth set. Two-minute breaks were allocated between each exercise`s third and fourth sets of and between exercises. Blood samples were collected from each participant 1 h after the completion of each trial. Data revealed no statistical difference (p ? .05) in ergogenic response to caffeine on sex hormones during the early follicular phase between trials. However, serum prolactin level significantly decreased (p = .039) after caffeine intake compared to the placebo. The overall repetitions to failure were significantly higher (p = .023) in the caffeine trial than in the placebo. In conclusion, caffeine intake (4 mg/kg) 1 h before multiple resistance exercises had no effect on sex hormone responses during the early follicular phase, except for prolactin. However, the overall repetitions until failure were higher following caffeine intake.